Improved magnetic behavior of hemicycle PM motor via stator modification - Kwang T. C.; Mohd Luqman Mohd Jamil; Auzani Jidin (Institute of Advanced Engineering and Science, 2020)
This article presents the simple basic sizing approaches to decrease overall weight of motor and improve magnetic characteristics in PM motor. A review on various stator design in PM motor i.e. radial-flux or axial-flux with slotted or non-slotted is presented. As magnetic and electric loading influence the electromagnetic motor performance, modification on stator body are included in investigation for a desired electromagnetic torque performance. Influences of tooth body width sizing and additional stator slots sizing in PM motor equip with hemicycle stator design are carried out. Two designs are included, both having similar semi-circle stator but different in additional slot tooth within and over 180 ○ i.e. Design 2 and 3 respectively. For optimization using 2D-Finite Element Analysis, optimal tooth body sizing and additional stator tooth result the weight significantly reduce by 44%, 5.9 Nm output torque and 30% torque ripple.